BRYDSON'S PLASTICS MATERIALS - Gilbert, Marianne editor 631932; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2017)
Brydson's Plastics Materials, Eighth Edition, provides a comprehensive overview of the commercially available plastics materials that bridge the gap between theory and practice. The book enables scientists to understand the commercial implications of their work and provides engineers with essential theory. Since the previous edition, many developments have taken place in plastics materials, such as the growth in the commercial use of sustainable bioplastics, so this book brings the user fully up-to-date with the latest materials, references, units, and figures that have all been thoroughly updated.